Analisis Pelayanan Anak Berkebutuhan Khusus Tipe Tunarungu Di Sekolah Inklusi SDN Gunungsekar 2 Sampang Madura - Moh. Sulaiman Romadhon; Nova Estu Harsiwi (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The aim of this research is to determine whether the services provided by the inclusive school SDN Gunungsekar 2 Sampang to deaf children are appropriate and successful or not. The research used in this research uses qualitative methods, qualitative methods are research procedures that produce descriptive data in the form of written or spoken words from people or observable behavior. The first stage is the preparation stage, the second stage is implementation, the third stage is data analysis and the final stage is reporting. The data collection methods used are observation, interviews and documentation. The subjects in this research were teachers as facilitators in teaching children with special needs, the deaf type at SDN Gunungsekar 2 Sampang. The results of the research are the implementation of services for deaf children even though there are many difficulties in learning, both from lack of teacher competence, as well as minimal learning facilities and infrastructure. Teachers at the elementary school continue to provide optimal support so that they continue to have comfortable and enjoyable learning and have a good impression on each of them.